KAJIAN IMPLEMENTASI OTONOMI KHUSUS DI PROVINSI PAPUA DALAM PERSPEKTIF EKONOMI KELEMBAGAAN BARU (NEW INSTITUTIONAL ECONOMICS) - Agustina Sanggrangbano (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2014)
Decentralisation specially in autonomy type is an example of institution changing occurs particularly in Indonesia. In the New Institutional Economics (NIE) perspective, institution role of the game in society is formal and informal which is used as a boundary in interaction between particular people. The existence of decentralisation is an effort to make a democratic governance system. In the New Institutional Economics perspective, the democratic governance system is not released from principal-agent relationship problem. The problem appears because the asymetric information existence, the non exsistence of checking and balancing mechanism, and the non exsistence of transparency between principal and agent. So the institution has a very important role in decentralizing governance system to make a successful development in a country. Keywords : New Institutional Economics, Institution, Principal-Agent, Special Autonomy